Observations of the Effects of Angiotensin II Receptor Blocker on Angiotensin II-Induced Morphological and Mechanical Changes in Renal Tubular Epithelial Cells Using Atomic Force Microscopy. (20th May 2018) - Kim, Jin Sug; Lee, Gi-Ja; Lee, Tae Won; Ihm, Chun Gyoo; Lee, Yu Ho; Kim, Yang Gyun; Moon, Ju-Young; Lee, Sang Ho; Kim, Ji-Hye; Kang, Sung-Wook; Chae, Su-Jin; Park, Hun-Kuk; et al.
Abstract : Objective. Angiotensin II (Ang II) plays a profibrotic role in the kidneys. Although many pathways of Ang II have been discovered, the morphological and mechanical aspects have not been well investigated. We observed the changes in tubular epithelial cells (TECs) after Ang II treatment with or without Ang II receptor blockers (ARBs) using atomic force microscopy (AFM). Methods. TECs were stimulated with Ang II with or without telmisartan, PD123319, and blebbistatin. AFM was performed to measure the cellular stiffness, cell volume, and cell surface roughness. Epithelial to mesenchymal transition markers were determined via immunocytochemistry. Results. After Ang II stimulation, cells transformed to a flattened and elongated mesenchymal morphology. Cell surface roughness and volume significantly increased in Ang II treated TECs. Ang II also induced an increase in phospho-myosin light chain and F-actin and a decrease in E-cadherin. Ang II coincubation with either telmisartan or blebbistatin attenuated these Ang II-induced changes. Conclusion. We report, for the first time, the use of AFM in directly observing the changes in TECs after Ang II treatment with or without ARBs. Simultaneously, we successfully measured the selective effect of PD123319 or blebbistatin. AFM could be a noninvasive evaluating strategy for cellular processes in TECs.